2018
DOI: 10.1155/2018/3984797
|View full text |Cite
|
Sign up to set email alerts
|

PTPN2 Downregulation Is Associated with Albuminuria and Vitamin D Receptor Deficiency in Type 2 Diabetes Mellitus

Abstract: Objective Inflammation plays a major role in albuminuria in type 2 diabetes mellitus (T2DM). Our previous studies have shown that the expression of vitamin D receptor (VDR) is downregulated in T2DM which is closely associated with the severity of albuminuria. In this study, we investigated the expression of anti-inflammatory cytokine protein tyrosine phosphatase nonreceptor type 2 (PTPN2) in T2DM and explored its relationship to albuminuria and VDR. Methods 101 T2DM patients were divided into three groups base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 42 publications
(44 reference statements)
0
14
0
Order By: Relevance
“…26 PTPN2 level in serum was much lower in T2DM patients than in healthy adults and negatively correlated with interleukin-6. 27 In this study, we found that the expression of PTPN2 was decreased in T2DM group around the implant in vivo and RBMSCs cultured in high glucose medium in vitro .…”
Section: Discussionmentioning
confidence: 57%
“…26 PTPN2 level in serum was much lower in T2DM patients than in healthy adults and negatively correlated with interleukin-6. 27 In this study, we found that the expression of PTPN2 was decreased in T2DM group around the implant in vivo and RBMSCs cultured in high glucose medium in vitro .…”
Section: Discussionmentioning
confidence: 57%
“…VDR plays an anti-inflammatory role in DN, but the mechanism of this function is not clear. Our previous study indicated that VDR exerts anti-inflammatory effects in high glucose-treated THP-1 cells via PTPN2 [25]. Zhang stress and excess nutrition induced by metabolic dysfunction in diabetes are implicated in autophagy impairment through alterations in the nutrient-sensing pathways, including AMPK, mammalian target of rapamycin complex1 and Sirt1 in renal cells [30].…”
Section: Discussionmentioning
confidence: 99%
“…In a 2018 study of Zheng et al [139] involving 101 patients, the Authors investigated the expression of anti-inflammatory cytokine protein tyrosine phosphatase nonreceptor type 2 (PTPN2) in DM patients and the relationship with VDR. They found out that paricalcitol administration increased PTPN2 expression by promoting its anti-inflammatory activities in case of high stimulation with glucose.…”
Section: Vitamin D and Diabetes In Kidney Diseasesmentioning
confidence: 99%